Efeito do treinamento muscular concêntrico e da flexibilidade nas propriedades musculotendíneas e na força muscular - Gustavo Henrique da Cunha Peixoto Cancado (2007)
Strength and flexibility training are widely used in various sports. However, studies about the effect of strength training using concentric action alone in the variables of flexibility capacity were not found in the literature. The aim of the present study was to analyze the effects of a 6 week strength training program using only concentric actions with or without the combined flexibility training of hamstring muscles in the variables maximal voluntary contraction (CVM), one repetition maximum (1RM), stiffness, energy, maximum range of motion (ADMmáx), maximum passive torque, subjective stretch tolerance (PSA) and integrated electromyographic activity (iEMG). Twenty-two male volunteers with a mean age of 23,0 ± 3,7 years, height of 176,5 ± 6,0 cm and a mass of 72,5 ± 10,0 kg participated of this study. Volunteers were randomly divided into concentric (n=12) and control (n=10) groups. The concentricgroup performed strength training for both lower limbs, while the right limb also performed a flexibility training (concentric_flex). The strength training consisted of 3 sets of 12 repetitions at 70% of 1RM, and at a frequency of 3 times per week. Flexibility training was performed twice a week, and in each section 4 sets of 20 second passive static stretch was performed. The control group did not perform any strength and flexibility training during the 6 weeks of this study. The results of the present study showed significant increase in the variables CVM and 1RM for the concentric. The concentric_flex group showed significant change in the variables CVM, 1RM, maximum ADM, maximum passive torque and PSA. All variables were unchanged in the control group. It can be concluded that strength training combined with flexibility training increases the variables of both capacities without other physical effects.